2004
DOI: 10.1179/146531204225020606
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of laceback ligatures: A randomized controlled clinical trial

Abstract: In first premolar extraction cases, the lower labial segment does not procline during the leveling stage with the pre-adjusted edgewise appliance and the use of laceback ligatures conveys no difference in the anteroposterior or vertical position of the lower labial segment. Furthermore, the use of laceback ligatures creates a statistically and clinically significant increase in the loss of posterior anchorage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…Usmani et al 3 observed the retroinclination of upper incisors with canine lacebacks. However, Irvine et al 4 found that canine laceback ligatures convey no differences in the anteroposterior position of the lower labial segment. In our study, two different force systems were used along the same arch wire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usmani et al 3 observed the retroinclination of upper incisors with canine lacebacks. However, Irvine et al 4 found that canine laceback ligatures convey no differences in the anteroposterior position of the lower labial segment. In our study, two different force systems were used along the same arch wire.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In two studies, the anteroposterior position of lower incisors was evaluated during the leveling and aligning stages. 2,4 Usmani et al 3 evaluated the anteroposterior position of upper incisors. However, a literature search showed that the effectiveness of lacebacks on canine distalization has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled clinical trial investigating the effectiveness of the laceback ligatures showed no statistical or clinical difference in the anteroposterior or vertical position of the lower labial segment or in the relief of labial segment crowding and the use of laceback ligatures creates a statistically and clinically significant increase in the loss of posterior anchorage, through mesial movement of the lower first molars [9]. In our case report, the laceback was used not in the way that McLaughlin and Bennett were intended but to apply gentle force to close the bony defect.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical control trial, canine lacebacks were found to prevent lower labial segment proclination in the order of 2.5 mm (19). However, it should be noted that the use of lacebacks have been questioned with a randomised control trial finding no difference of canine lacebacks to prevent lower incisor proclination but found a statistically significant difference of more mesial movement of the molars (20). Thus, in order to reduce the amount of mesial movement of the molars, the lower second molars were also included in the canine lacebacks to increase the posterior anchorage.…”
Section: Discussionmentioning
confidence: 99%